2012
DOI: 10.1021/bm300590x
|View full text |Cite
|
Sign up to set email alerts
|

Engineered Mutations Change the Structure and Stability of a Virus-Like Particle

Abstract: The single-coat protein (CP) of bacteriophage Qβ self-assembles into T = 3 icosahedral virus-like particles (VLPs), of interest for a wide range of applications. These VLPs are very stable, but identification of the specific molecular determinants of this stability is lacking. To investigate these determinants along with manipulations that confer more capabilities to our VLP material, we manipulated the CP primary structure to test the importance of various putative stabilizing interactions. Optimization of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
89
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(95 citation statements)
references
References 72 publications
6
89
0
Order By: Relevance
“…Pleasingly, Qβ-CS still formed discrete particles, even without disulfide bonds at C74 and C80 (Figure S2), consistent with prior studies that have identified the dominant contribution of noncovalent interactions between viral subunits. 34 The relative robustness of these Qβ-CS VLPs was probed with 19 F-NMR: in contrast to Qβ-F, Qβ-CS VLPs disassembled directly into monomers under denaturing conditions when treated only with SDS (Figure 2c), consistent with our intended design. The chemical shifts of Qβ-CS VLPs in the absence and presence of SDS were highly similar (−40.63 ppm, FWHH = ∼200 Hz; −40.88 ppm, FWHH = ∼6 Hz, respectively) to those observed for Qβ (Figure 2b).…”
supporting
confidence: 65%
“…Pleasingly, Qβ-CS still formed discrete particles, even without disulfide bonds at C74 and C80 (Figure S2), consistent with prior studies that have identified the dominant contribution of noncovalent interactions between viral subunits. 34 The relative robustness of these Qβ-CS VLPs was probed with 19 F-NMR: in contrast to Qβ-F, Qβ-CS VLPs disassembled directly into monomers under denaturing conditions when treated only with SDS (Figure 2c), consistent with our intended design. The chemical shifts of Qβ-CS VLPs in the absence and presence of SDS were highly similar (−40.63 ppm, FWHH = ∼200 Hz; −40.88 ppm, FWHH = ∼6 Hz, respectively) to those observed for Qβ (Figure 2b).…”
supporting
confidence: 65%
“…One common technique to improve particle thermostability is the introduction of intersubunit disulfide bonds. For instance, mutations that introduce cysteines at the 5-fold symmetry axes increase the stability of MS2 VLPs [34,35]. Similarly, Hepatitis B core antigen VLPs with enhanced stability were produced by identifying amino acid pairs of interacting dimers with the shortest distances between side chains and substituting cysteines that could form disulfide bonds, creating a disulfide-bond network stabilizing the particle [36].…”
Section: Engineering More Stable Vlpsmentioning
confidence: 99%
“…In contrast, very few attempts aimed at the rational thermostabilization of FMD virions (Mateo et al, 2008) or capsids (Porta et al, 2013b), other virus particles (Ashcroft et al, 2005;Fiedler et al, 2012) or supramolecular assemblies, have been published so far. This situation severely impairs the establishment of structure-based protein engineering guidelines for developing robust virus particles and protein assemblies for different applications (Mateu, 2011).…”
Section: Introductionmentioning
confidence: 99%